Load Flow Analysis After the Entry of Renewable Power Plants in the Sulselrabar System - Muhammad Ruswandi Djalal; Makmur Saini; A.M Shiddiq Yunus (Journal of Electrical Technology UMY, 2021)
Power flow analysis in an electric power system is an analysis that reveals the performance of an electric power system and the flow of power (active and reactive) for certain conditions when the system is working. The analysis was carried out using the ETAP 16.00 software, the method used was the newton rapshon by taking a case study of normal conditions. From the results of the study, it can be seen that the power flow that occurs in each channel of the 150 kV system in the South Sulawesi system. The amount of active power (MW) that occurs during normal conditions based on the simulation is 1730.87 MW, where the active power is the largest, which is 171 MW from BUS15_TLASA to BUS13_SGMNSA. For the voltage data, there is a slight comparison of the voltage during the simulation compared to the PLN data.